Implementation Of Trait And Factor Theory In Improving Students' Career Understanding: Literature Review - Setyorini, Ragil; Daharnis; Ifdil (Yana Research, 2025)
Students' career understanding, especially at the high school level, is often a significant challenge due to their lack of knowledge about their potential and the world of work. This study aims to analyze the implementation of Trait and Factor theory in improving students' career understanding through literature review. The research method used is literature review by collecting, evaluating, and synthesizing related literature from relevant journals, books, and scientific articles. Data sources were selected based on relevance to the topic, recency, and academic validity. The results showed that the Trait and Factor approach is effective in helping students understand their potential, reduce career confusion, and improve career decision-making ability. Through systematic guidance and counseling services, this approach facilitates students to match their personal characteristics with the demands of the world of work. In addition, counselors play a strategic role in providing assessment, career information, and ongoing support to students to achieve appropriate career decisions. The conclusion of this study confirms that Trait and Factor theory can be a strong foundation in the implementation of career counseling services to improve students' career understanding. Proper implementation of this approach not only helps students in making career decisions but also prepares them for the challenges of transitioning to the world of work or higher education.